AUX/LAX family of auxin influx carriers—an overview - Swarup, Ranjan; Péret, Benjamin (Frontiers in Plant Science, 2012)
Auxin regulates several aspects of plant growth and development. Auxin is unique among plant hormones for exhibiting polar transport. Indole-3-acetic acid, the major form of auxin in higher plants, is a weak acid and its intercellular movement is facilitated by auxin influx and efflux carriers.. Polarity of auxin movement is provided by asymmetric localisation of auxin carriers (mainly PIN efflux carriers). PIN-FORMED (PIN) and P-GLYCOPROTEIN (PGP) family of proteins are major auxin efflux carriers whereas AUXIN1/LIKE-AUX1 (AUX/LAX) are major auxin influx carriers.. Genetic and biochemical evidence show that each member of the AUX/LAX family is a functional auxin influx carrier and mediate auxin related developmental programmes in different organs and tissues. Of the four AUX/LAX genes, AUX1 regulates root gravitropism, root hair development and leaf phyllotaxy whereas LAX2 regulates vascular development in cotyledons. Both AUX1 and LAX3 have been implicated in lateral root development as well as apical hook formation whereas both AUX1 and LAX1 and possibly LAX2 are required for leaf phyllotactic patterning.